CLIL AND ENGLISH TEACHERS’ COMPETENCIES IMPROVEMENT - Agustrianti, Sawitri (Paedagogia: Jurnal Pendidikan, 2016)
Content language integrated learning (henceforth CLIL) is widely considered as an innovative approach in the present and future foreign language learning (English). CLIL is the integration of language with the content in learning environment which increases students’ competence, motivation, and intercultural awareness. In many studies, CLIL is explained based on the advantages and limitation toward students learning process, however, only few studies examine the implication of CLIL toward teachers’ competence in the classroom. Therefore, this paper aims to fill the gap by examining how CLIL has implications to improve English teacher competencies in EFL context. This paper addresses CLIL in the framework of definition and rationale, CLIL dimension and methodology, the advantages of CLIL, and the implications of CLIL toward teachers’ professional competencies. In line with the implications, this paper mainly focuses on personal reflection, content and language awareness, methodology and assessment, research and evaluation, and learning resources and environments. Additionally, in the methodology, it points out at building students’ capacity, co-operating with other teachers, building direction and focus, building safe and meaningful learning experiences, and assessing. Last, this paper presents conclusions and suggestions for potential CLIL teachers.